Safety and Efficacy of Mechanical Thrombectomy Using Tigertriever as a Rescue Device After Failed Aspiration—Single Center Experience - Piotr Piasecki (Frontiers in Neurology, 2021)
Introduction: We evaluated the safety and efficacy of a new stent retriever—Tigertriever—after failed aspiration.Materials and Methods: Patients with acute ischemic stroke treated with Tigertriever between January 2018 and March 2020 were included in the study. Treatment results of Tigertriever in rescue therapy (after failed aspiration) were evaluated. Periprocedural data were retrospectively analyzed.Results: Thirty patients were treated with Tigertriever (14M/16F). There were 20 rescue thrombectomies after failed aspiration. Tigertriver successful recanalization rate (mTICI ≥ 2B) was 70%: 65% in rescue therapy and 80% in first-line therapy. The type of first line treatment had no impact on mRS after 1 month and 3 months (ns). There was significant improvement in NIHSS in all patients (mean NIHSS: 17 vs. 10, p = 0.028), in rescue treatment (mean NIHSS: 17 vs. 11, p = 0.048) and in first line treatment (mean NIHSS: 16 vs. 8, p = 0.0005). Better results in NIHSS at discharge were linked with first pass success (p = 0.002), better mTICI at the end of the procedure (p = 0.0006), and administration of rtPA (p = 0.013).Conclusions: The new stent retriever Tigertriever is an efficient and safe tool to be used as a rescue device after an unsuccessful first line aspiration technique.